Letter: thiopurines ‐ is less really more? Authors' reply. Issue 1 (11th December 2017) - Roblin, X.; Paul, S.; Nancey, S.; Flourie, B.
Abstract : Linked Content This article is linked to Roblin et al papers. To view these articles visithttps://doi.org/10.1111/apt.14106 andhttps://doi.org/10.1111/apt.14375 .